Occupational Health and Safety Risks in the Shipbuilding Industry, Case Study at PT Blambangan Bahari Shipyard - Iya Purnama Sari; Aufa Ilasabilirrosyad; Yulia Estmirar Tanjov; Siti Mira Rahayu (Buletin Jalanidhitah Sarva Jivitam, 2023)
The shipbuilding industry is a useful place for producing or even repairing ships. PT Blambangan Bahari Shipyard in this study is one of the shipbuilding industries which is a shipbuilding company and shipping consultant. Occupational safety in every workplace, including in the ship production sector, needs to be considered to reduce the risk of work accidents as low as possible. This research aims to identify the types of hazards or analyze risks in shipbuilding activities with case studies at PT. Blambangan Bahari Shipyard. This study uses a quantitative approach with a criterion scale to analyze data from interviews and risk observations at each stage of shipbuilding. Then the data were analyzed using the Hazard and Operability Study (HAZOP) method. The results of the risk analysis of the shipbuilding process show that the stages of mold making, mold coating, gel coat and lamination have a high-risk level. This is because, at this stage, many workers use tools that are quite dangerous for them. In addition, the risk analysis results show that the shipbuilding process has a high level of risk in terms of work safety. The high risks experienced by workers are exposure to electric drills, electric shock, eye pain, skin irritation, respiratory problems, and bronchitis.